Prevalence of Elevated Lipoprotein A (Lp(A)) in Nepalese Patients with Traditional Risk Factors of Atherosclerotic Cardiovascular Disease (ASCVD) - Adhikari, Suman; Poudel, Rajendra; Hamal Thakuri, Surya Bahadur; Baral, Shankar; Nepal, Choodamani; Dhungana, Umesh; Budha, Arjun Kumar; Rawat, Gobind; Ghimire, Sunita; Devkota, Sandesh; Sharma, Manju; Ghimire, Deen Dayalu; et al. (Nepalese Heart Journal, 2025)
Background and aims: One important residual CVD risks is elevated level of lipoprotein a (Lp(a)). High Lp(a) level is atherogenic. It’s higher prevalence in South Asian population is important because of a higher prevalence of premature coronary artery disease in younger population of this region. Lp(a) testing is underutilized. Knowing elevated levels in an individual may help address and control traditional risk factors of ASCVD in such patients. Methods: This study was an observational, prospective study carried out in the department of internal medicine, Pokhara Academy of Health Sciences(POAHS), Nepal. The study was started on 17th September 2023 and completed on 16th March 2024. The details of history and the physical examination of cases were recorded in the proforma designated for the study. Baseline data were recorded including age, sex, presence of risk factors like diabetes mellitus(DM), hypertension(HTN), dyslipidemia, smoking, history of CAD (coronary artery disease) and coronary revascularization, family history of premature CAD, lab parameters like blood glucose, lipid profiles, Lp(a), ECG, echocardiography, coronary angiography. Statistical analysis was carried out with the help of the latest version of SPSS. Results: The mean age was 48.52 years (SD=9.06). Majority were (56%) male patients. 42 cases (84%) were dyslipidemics and 26 (52%) were hypertensives, 10 cases (20%) had family history of coronary artery disease in first degree relatives, 10(20%) had coronary artery disease, eight (16%) had DM, two (4%) were smokers. Elevated Lp(a) (>/=50mg/dl) was found in 14(28%) of total cases. Of total cases, Lp(a) was <20mg/dl in 30 (60%), 20-49mg/dl in 6(12%) and thus Lp(a) >/=20 mg/ dl was observed in 40% of cases. Conclusion: The prevalence of elevated Lp(a) in Nepalese patients with traditional risk factors of ASCVD is high. These findings from our study may carry important implications for clinical practice in Nepal. Performing targeted screening in high-risk individuals may help redefine risk category and may help in aggressively managing traditional risk factors